Fertility Status of the Soil in the Area Where Rubber (Hevea brasiliensis) Plants are Being Replanted (Elaeis guineensis Jacq) - Prayuda, Dedek; Harahap, Fitra Syawal; Walida, Hilwa; Dalimunthe, Badrul Ainy (Universitas Sembilanbelas November Kolaka, 2023)
Rubber plants (Hevea brasiliensis) will experience a decrease in production as plant age and the nutrient content in the soil decreases. This study aims to find out the chemical properties of soil on plantations of rubber crops that are converted into palm and coconut crops. The research was conducted from October 2023 to January 2024 at the palm coconut plantation of PTPN III Aek Nabara North Garden in Labuhanbatu district and analyzed in the Land Laboratory of the Faculty of Agriculture of the University of Northern Sumatra. The methods used are observation methods, field sampling, and analysis in the laboratory to obtain quantitative data. Observation parameters include soil pH, C-organic, Total Nitrogen, Available P, Cation Interchange Capacity, and Base Fulness. The results of the survey showed that the level of soil fertility at the site of the research was included in the low category. The main limiting factor that causes the low fertility of the soil is the low content of organic material in the soil. In order to improve the fertility status of the ground at the research site for further planting, it is necessary to make efforts such as irrigation and fertilization, as well as the addition of organic materials, to make the availability of nutrients for plants more affordable